Селянські промисли з переробки тваринної сировини на Харківщині в роки НЕПу - Лапченко, А.С. (Історичний архів. Наукові студії, 2015)
Основну увагу в статті приділено висвітленню особливостей географічно-галузевого оформлення дрібного виробництва з тваринної сировини регіону в 20-х рр. ХХ ст. На основі виявленого і вивченого автором комплексу джерел проаналізовано джерельну базу селянських промислів на Харківщині в зазначений період. Установлено загальну кількість селян, які займалися промислами з обробки тваринної сировини. Також виявлено специфіку промислової діяльності харківського селянства протягом НЕПу. Акцентовано увагу на характерних рисах державної політики щодо «малого бізнесу» селян. Приділено увагу кооперуванню цих промислів та наслідкам на подальший розвиток. Основное внимание в статье посвященно освещению особенностей географически-отраслевого оформления мелкого производства из животного сырья региона в 20-х гг. ХХ в. На основе обнаруженного и изученного автором комплекса источников проанализировано источниковедческую базу крестьянских промыслов на Харьковщине в указанный период. Установлено общее количество крестьян, которые занимались промыслами по обработке животного сырья. Также выявлена специфика промышленной деятельности харьковского крестьянства в течение НЭПа. Акцентировано внимание на характерных чертах государственной политики относительно «малого бизнеса» крестьян. Уделено внимание кооперированию этих промыслов и последствиям. Background research related to the lack of researches in the given topic historiography. Territorial boundaries cover a large region – Kharkiv region, which until 1925 largely coincide with the boundaries of Kharkov province. And in 1925, it was divided into several provinces – Kharkov, Sumy, Kupiansk, Izyumskogo, Romney. The chronological boundaries article dated from 1921–1929’s, during which was implemented new economic polityka.Osnovnu attention paid to the article features geographically-sectoral design small-scale production of animal products in the region in 20 years of the twentieth century. On the basis of the detected and studied complex of sources the author analyzes the source base peasant industries in Kharkiv in this period. Found total number of farmers who were engaged in crafts processing animal products. Also revealed the specific industry Kharkov peasantry during nepu.Isnuvav number of factors that pushed the peasant engage in crafts: surplus agricultural products and raw materials; meet a wide range of numerous industrial, domestic and cultural needs; urgent need to replenish the family budget; surplus labor; free time from agricultural work (especially in winter) and others. The development of rural industries processing animal products in the years 1921–1929 in the Kharkiv region characterized by strength and diversity. Village artisans representing an original way of small private commodity production. Basically crafts processing animal products involved in two socio-professional groups: lone artisan and peasant host of crafts. The social basis of industrial
employment accounted malozemelni without sowing without Traction economy, which crafts were an important source of household income. The attention is focused on characteristic features of the state policy on «small business» peasants. Attention is paid to co-operation and effects of these industries on the further development rozvytok.Kooperatyvna form does not become dominant and dominant. In the 1927–28 biennium. 33 % were co-rural artisans, engaged in crafts processing animal products in Kharkiv.